(untitled) (Journal on studies and research of academic knowledge, 2016)
homes and industries, which aims to remove contaminants and to make them suitable for other uses, or to avoid environment damages. However, this treatment results in the formation of residual sludge, and with it the consequence of unpleasant odors, so it should be an appropriate treatment of sludge that imply an extra cost in its handling and disposal. This work proposes to give an alternative solution to the management of aerobic residual sludge, testing it as inoculum in the start of an anaerobic reactor and also, using it directly as biofertilizer. This work demonstrated that the residual aerobic sludge of the treatment plant when subjected to anaerobic reactor during 25 days has an important methanogenic activity, identifying through microbiological analysis the presence of methanogenic bacteria such as Metanococcus and Metanobacterium, indicating that could be used as an inoculant of bioreactors for the generation of biogas with some type of substrate that provides the organic matter necessary for biotransformation. The physicochemical parameters analyzed are within the allowed ranges for this type of sludge according to the Mexican Standard Enviromental Protection sludge and biosolids 004-SEMARNAT 2002 As for the efficacy of the aerobic residual sludge as a biofertilizer placed directly (without having been thickened, digested or dehydrated). the low emergence of Lactuca sativa seeds was verified only 5.3% and mixtures of this was 40.6% compared to a control soil of 86% of germinated seeds.